Covid-19 & Stigma of Patient Families and Health Workers in Makassar City, Indonesia - Abdul Gafur; Zainuddin Zainuddin; Musdalifah Musdalifah; Safriadi Darmansyah (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2021)
Covid-19 has now become an epidemic that has spread almost all over the world and has caused morbidity and mortality. covid-19 in addition to having an impact on physical health also has an impact on the social and economic life of the community as well as mental disorders due to the stigma experienced by infected people, families, and health workers. This study aims to determine the role of knowledge about community stigma towards health workers and families of covid-19 patients in Makassar City, Indonesia. In this study using a quantitative method with a descriptive survey approach, the sample in this study was 105 respondents, which were taken by simple random sampling technique. The study found that public knowledge about covid-19 was related to stigma in the families of covid-19 patients (p=0.010) and knowledge was also associated with stigma to health workers (p=0.000). Stigma against families and health workers still occurs in Makassar City, due to the lack of knowledge possessed by the community and the existence of fake news or hoaxes that trigger the emergence of stigma against health workers and families of covid-19 patients.